The difference of knowledge and primary preventive for typhoid fever between parents in rural and urban areas to children under-five ages - Yushi Rohana (Universitas Airlangga, 2017)
Children under five ages are vulnerable to infectious disease, one of which is typhoid fever. Typhoid fever is a disease caused by infection of Salmonella typhii and Indonesia is endemic typhoid fever. So that the toddler has not been suffered from typhoid fever, it needs participation of their parents to prevent them from the occurrence of the disease. The aim of this research was to analyze the difference between knowledge and parents's action in preventing typhoid fever of their children in rural and urban areas. This type of this research is observational analytic with design of study is cross sectional. The population is parents of children under five ages in rural and urban areas. Samples of this research was ECE's that taken by one stage cluster random sampling. The number of samples in the rural area were 51 parents of children under five ages and the number of samples in urban were 54 parents of children under five ages. The collection of data used a questionnaire to parents of children under five ages. Data analysis techniques used two independent samples t test and Wilcoxon Mann-Whitney test. The results of this study that there were difference in knowledge of typhoid fever for parents of children under five ages in the rural and urban area (p = 0.014), there are differences in the primary preventive against in typhoid fever between parents in rural and in urban areas (p = 0.0001), and there are difference in secondary prevention against typhoid fever between parents in rural and in urban areas (p = 0.0001). The conclusion of this research isthere are differences in knowledge and actions of parents in rural and urban areas in preventing typhoid fever in children under five ages. The suggestion for parents of children under five ages is attention and increase hiegiene and sanitation to avoid typhoid fever and they should teach their children to always keep clean Keywords : knowledge, prevention, typhoid fever, children under five ages